Unpublished Administrative Ostraca from Gurna - Ewais, Marwa Ahmed (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
The present paper deals with some hieratic ostraca from Gurna, stored in the National Museum of Egyptian Civilization in Cairo (NMEC). These ostraca are written on one side only, with black ink. They were found during the excavations led by Edda Bresciani in the 1970s from Thutmose IV’s temple at Gurna together with other ostraca written in different scripts: Demotic, Greek, and Coptic. The ostraca are administrative, and their topics are various. According to the content, as well as the paleography of script, these ostraca probably date to the 18 th Dynasty and the Ramesside period. O. NMEC No. 409 and O. NMEC No. 339 probably date to the 18 th Dynasty while O. NMEC No. 406, O. NMEC No. 342, and O. NMEC No. 449 are dated to the Ramesside period.